Determinan Kepatuhan Wajib Pajak Bumi Dan Bangunan (PBB) Dalam Membayar Pajak Di Kecamatan Medan Amplas Kota Medan - Chaniago, Muhammad Arif; Jayusman, Sri Fitria; Munawaroh (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
The problem of this research is that knowledge, awareness and sanctions of Land and Building Tax have an effect on paying taxes in Medan Amplas District. This research method uses quantitative methods with a sample of 99 people, data collection techniques using questionnaires and statistical data analysis using SPSS. The results of this study illustrate that there is an effect of knowledge on compliance with paying PBB as a result of calculations at a significance level of 0.05% where n=99 is 7.321 or t-count 7.321 > 1,660, there is an influence of awareness on compliance with paying PBB as a result of calculations at a significance level of 0.05% where n = 78 is 4.242 thus t-count 4.242 > 1,660, there is an effect of sanctions on compliance with paying PBB as the result of calculations at a significance level of 0.05% where t-count is 2.300 > 1,660. There is the influence of knowledge, awareness and sanctions simultaneously on paying Land and Building Tax in Medan Amplas District, as Fcount is 46.368 > Ftabel 1.95 with a significant level of 0.05. Because Fcount is greater than Ftabel , it is concluded that knowledge, awareness and sanctions simultaneously have a positive and significant effect on compliance with paying PBB in Medan Amplas District with the level of influence based on the determinant test of 80,8%.